Primary School Teachers’ Competence Level in The Early Identification of Gifted Children - Usman Tunde Saadu; K. E. Obafemi; Adeyemi Christianah Oluwakemi (Indonesian Journal of Community and Special Needs Education, 2024)
The research explores the competence of teachers in recognizing and differentiating gifted students from their peers, which is crucial for providing appropriate educational interventions and support tailored to their unique needs. The methodology employed a descriptive survey design, with data collected through a questionnaire. The sample consisted of private and public primary school teachers in the area. The findings indicate a low competence level among primary school teachers in the early identification of gifted children. The study found no significant differences in competence based on gender or school type. However, there was a significant difference in competence based on teacher qualification, with those holding M.Ed./M.Sc. qualifications showing a higher level of competence. Overall, the study highlights the need for targeted professional development and support for primary school teachers in the identification of gifted children. By improving teachers' competence in this area, it is possible to enhance educational interventions and provide appropriate support to nurture the potential of gifted students.